Efficient photovoltaics integrated with innovative Li-ion batteries for extreme (+ 80 oC to −105 oC) temperature operations - Ethan Adams; Alexander Camacho; Evan Mammana; Soohwan Kim; Thomas E. Adams; Vilas G. Pol (Scientific Reports)
Abstract Current pursuits for further exploration into extreme environments like aerospace, outer space, and Arctic conditions require matching energy harvesting and storage technologies that can efficiently operate in extreme conditions. While current systems utilize a variety of different battery chemistries, photovoltaics, and radioisotope power systems to power and store the required energy, at ultra-low temperatures (<-60 °C), current batteries have extremely low-capacity retention (< 20 %) and require extensive heating coils and thermal shielding to work when paired with photovoltaics. To simultaneously test both current and new types of whole photovoltaics (PV) and innovative Li-ion batteries (LIBs) at extreme temperatures (180 °C to -185 °C) in the research laboratory, an Integrated Photovoltaic and Battery (IntPB) system has been developed at Purdue University. The first IntPB allows for testing a variety of energy storage devices (Li-ion, Na-ion, K-ion batteries) and harvesting technologies (PV, radioisotope, thermoelectric), verifying their suitability when paired at a wide range of temperatures and charging protocols. A specially designed IntPB system allowed for testing either small-scale coin cells (10 mAh) or larger pouch cells (1 Ah) with polycrystalline silicon PV between 80 °C to -120 °C. It effectively charged the lithium metal battery using a niobium tungsten oxide cathode and 1 M LiFSI in cyclopentyl methyl ether electrolyte to comparable capacities. When discharged with the battery cycler, the battery provided similar capacities at a constant current discharge, thus ensuring that the system was able to charge/discharge equivalent amounts of energy. At 80 °C, -105 °C, and − 120 °C, the IntPB was able to charge/discharge 150 mAh g⁻¹, 30 mAh g⁻¹, and 6 mAh g⁻¹ capacity, respectively. This indicated that the pairing of the PV and battery was able to charge/discharge the battery at a wide range of temperatures that the system would be expected to experience in places such as the desert, Arctic, or outer space. Contrasting temperature effects in integrated PV-battery systems pose a significant challenge: PV efficiency improves at low temperatures due to increased semiconductor band gap, while LIB performance deteriorates due to sluggish Li-ion movement within the electrolyte and across interfaces, necessitating careful system optimization to balance enhanced PV output with limited battery storage capacity.